PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR KAWASAKI (Studi Kasus Pada Konsumen Sepeda Motor Kawasaki di Kendal) (Students' Journal of Economic and Management, 2016)
This study analyzed the effect of brand image, product quality, and price on purchase decisions Kawasaki motorcycle (a case study on consumer Kawasaki motorcycle in Kendal). Sampling technique in this study of 100 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing questionnaires to the respondents in order to obtain information. The research objective formulated to determine the effect of brand image, product quality, and price on purchase decisions Kawasaki motorcycles. Data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The results of the research are: (1) the brand image has a positive and significant influence on purchasing decisions Kawasaki motorcycle. (2) the quality of the product has a positive and significant influence on purchasing decisions Kawasaki motorcycle. (3) price has a significant positive influence on purchasing decisions Kawasaki motorcycle Keywords: brand image, product quality, pricing and purchasing decisions